Low-infrastructure artificial insemination laboratory "mobile kit" (part of reproductive platform to support and scale goat breeding programs in Ethiopia and Tanzania) - CGIAR Research Program on Livestock (2018)
The platform is a real entity materialized with 3 labs, several people trained, confirmed synchronization protocols, regular insemination rounds supporting CBBP and we have spillovers in Sudan